Number of drugs provided by the Pharmaceutical Benefits Scheme and mortality and hospital utilization in Australia, 2002-2019 - Frank R. Lichtenberg (Elsevier, 2023)
We analyze the relationship between long-run changes in the drugs provided by the Pharmaceutical Benefits Scheme (PBS) and mortality and hospital utilization in Australia, by analyzing the correlation across diseases between the change in the number of drugs used to treat the disease provided and the subsequent change in mortality or hospital utilization from that disease.Our estimates indicate that diseases for which there were larger increases in the number of PBS drugs tended to have smaller subsequent growth in premature (before ages 85, 75, and 65) mortality. Diseases for which there was larger growth in the number of PBS drugs also tended to have smaller growth in the number of hospital days 2-10 years later. The reduction in the number of hospital days appears to be primarily attributable to a reduction in average length of stay.We estimate that the 1996-2013 increase in the number of PBS drugs was associated with a reduction in the number of years of life lost before age 85 in 2019 of 359,026, and that the 1994-2011 increase in the number of PBS drugs was associated with a reduction in the number of hospital days in 2019 of 2.48 million. A rough estimate of the cost per life-year before age 85 gained in 2019 from drugs previously added to the PBS is $AUS 1388.